Advances in improved/enhanced oil recovery technologies for tight and shale reservoirs. (15th December 2017) - Wang, Lei; Tian, Ye; Yu, Xiangyu; Wang, Cong; Yao, Bowen; Wang, Shihao; Winterfeld, Philip H.; Wang, Xu; Yang, Zhenzhou; Wang, Yonghong; Cui, Jingyuan; Wu, Yu-Shu
Abstract: This paper presents a comprehensive review of the technical progress as well as updated knowledge and understandings of IOR/EOR technologies for tight oil reservoirs. Critical and in-depth assessment of various IOR/EOR methods is made upon the best practice and lessons learned, mainly, in the North America. In the past few years, many traditional and new IOR/EOR methods have been tested in laboratory and piloted in field to investigate their potential in improving oil recovery from unconventional plays, including water injection, miscible and immiscible gas injection, water-alternating-gas injection, chemical flooding, and nanotechnology. Feasibility concerns and technical challenges, such as low injectivity, formation damage, and low sweep efficiency arising from extremely low permeability and high heterogeneity in fractured tight oil reservoirs, are raised for directly adopting traditional IOR/EOR methods. IOR/EOR mechanisms in tight oil reservoirs mainly involve gas and oil flows in nanometer pores, gas dissolution and diffusion through low permeability matrix, oil swelling, wettability alteration, IFT reduction, and fracture-matrix interaction, thus thorough understanding of flow and transport mechanisms in multi-scale pores and fractures is indispensable for developing effective IOR/EOR technologies. To optimize the selection of specific gas species or chemical formulas, it is necessary to conduct preliminary assessment of practicability and viability with both experimental studies and numerical simulations for operation upscaling and production prediction before field implementation.